2017
DOI: 10.1038/s41598-017-02576-5
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin and Bezafibrate ameliorate Emotional disorder Induced by High fat diet in C57BL/6 mice

Abstract: High fat diet (HFD)-induced metabolic disorders may lead to emotional disorders. This study aimed to explore the effect of simvastatin (SMV) and bezafibrate (BZ) on improving HFD-induced emotional changes, and tried to identify their different mechanisms. The intraperitoneal glucose tolerance test (IPGTT) was used to evaluate glucose control ability; and behavior tests including open field tests (OFT), forced swimming tests (FST), tail suspension tests (TST) and sucrose preference (SPT), were then performed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…1a). The HFD and ND groups also formed different clusters, which is consistent with previous reports [17,37]. Moreover, hierarchical clustering of the heatmap revealed striking changes in the genera resulting in distinct clustering of the samples (Fig.…”
Section: Resultssupporting
confidence: 91%
“…1a). The HFD and ND groups also formed different clusters, which is consistent with previous reports [17,37]. Moreover, hierarchical clustering of the heatmap revealed striking changes in the genera resulting in distinct clustering of the samples (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Some research showed that LPC and LPE are increased in inflammation associated diseases, and they exert their effects through different signaling pathways such as PKC, NF-κB and ERK (Zeng et al, 2017). While in other studies, some of the LPC and LPE were decreased in the inflammation condition (Bai et al, 2014;Zhou et al, 2014;Qian et al, 2017;Wang et al, 2017). In this study, several LPC and LPE were decreased with the decreasing dietary FM levels, which indicated the relationship of inflammation and the levels of LPC and LPE may dependent on species and the inflammation stage.…”
Section: Discussionmentioning
confidence: 97%
“…Patients presenting mood disorders show elevated plasma levels of cytokines such as TNF-α, IL-6, and IL-1β, as well as increased expression of inflammatory markers in blood cells (reviewed by Mechawar and Savitz, 2016). Increased consumption of high fat diet is related to depressive-like behavior and emotional disorders in mice (Wang et al, 2017; Arcego et al, 2018; Vagena et al, 2018; Xu et al, 2018), and neuroinflammation could be an important modulator of these behavioral alterations. Palmitic acid abolished the migration and phagocytic activity of microglia in response to interferon-γ, thus affecting the protective response of these cells after an inflammatory challenge in vitro (Yanguas-Casás et al, 2018).…”
Section: Saturated Fatty Acids and Neuroinflammation: Possible Linksmentioning
confidence: 99%